Implementation of Securing Data in the Cloud using Combined Cryptography and Steganography - Rosalina Rosalina; Nur Hadisukmana (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
The recent advance in information technology field forcing us to ensure the privacy of the digital data. It is very important to develop the method that may satisfy the needs. Many methods/techniques applied to reach that goal. One of efficient way to reach that secrecy can be achieved with implementing steganography. TheStego application is using Steganography to work in the digital domain and hides the data information within speech signal. To increase the security, TheStego combines steganography techniques with MD5 encryption techniques. Steganography techniques that applied in TheStego application is using LSB (Least Significant Byte) method. This application have three main features: hide text in an audio carrier, hide image within the audio and an audio inside a wave signal of an audio carrier. TheStego also required the user to enter password before the processing of data hiding begin. The password will act as decryption password. Such approach is implemented to increase the security of this application. So, only the one who knows the password that can extract and decrypt the data inside of the application.